2014
DOI: 10.21273/hortsci.49.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Botrytis cinerea and Quality Characteristics during Storage of Raspberry Genotypes

Abstract: Raspberries are a delicate, high-value crop with an extremely short shelf life exacerbated by postharvest decay caused by Botrytis cinerea Pers. European red raspberry (Rubus idaeus L.) is the most widely grown variety. Yellow (R. idaeus L.), black (R. occidentalis L.), and purple raspberries (R. ×neglectus Peck. or R. occidentalis ×idaeus hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For instance, strawberries illuminated with white fluorescent light showed increased anthocyanin content and delayed development of grey mould (Saks et al , ). Reduced fruit decay has also been observed in raspberries with high pigmentation (Harshman et al , ) and in transgenic tomatoes that accumulate anthocyanins (Bassolino et al , ; Zhang et al , ). Other small phenolics, especially catechins, may have a role in quiescence.…”
Section: Strawberry‐botrytis Cinerea Pathosystemmentioning
confidence: 96%
“…For instance, strawberries illuminated with white fluorescent light showed increased anthocyanin content and delayed development of grey mould (Saks et al , ). Reduced fruit decay has also been observed in raspberries with high pigmentation (Harshman et al , ) and in transgenic tomatoes that accumulate anthocyanins (Bassolino et al , ; Zhang et al , ). Other small phenolics, especially catechins, may have a role in quiescence.…”
Section: Strawberry‐botrytis Cinerea Pathosystemmentioning
confidence: 96%
“…In our study, B. cinerea was detected at pea size, a phenological stage where the content of phenols and organic acids is high (Nunan et al, 1998). This is significant because during pea size growth stage, pathogen proliferation is compromised (Harshman et al, 2014;Jia et al, 2016), further confirming the sensitivity of the ddPCR, as shown in previous work (Dreo et al, 2014). It is also important to note that pyrosequencing analysis of the same samples used in our present study did not detect B. cinerea (Carmichael et al, 2017), showing that ddPCR was more sensitive in this regard.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, susceptibility of the berries to pathogen incidence is enhanced during the ripening process. This is due to a decrease in phenolic compounds and organic acids in berries as well as other deciduous fruit (Padgett and Morrison, 1990;Deytieux-Belleau et al, 2009;Harshman et al, 2014;Jia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they produce an off flavor and foul smell due to the production of anaerobic products such as ketones, aldehydes, alcohols, lactic acid, and ethanol (Ellis et al., 2008; Moor et al., 2014). Pathogen‐mediated stress increases color modifications in Rubus berries due to the oxidation of anthocyanins and phenolics, while reducing oxygen radical absorbance capacity (ORAC) assay (Harshman et al., 2014). Overall, a higher proportion of fruit is rejected by consumers just because of 3% decay symptoms on fruit surfaces (Bell et al., 2021).…”
Section: Factors Affecting Postharvest Fruit Qualitymentioning
confidence: 99%
“…I G U R E 5 Relationship between different postharvest factors affecting the storability and shelf life of Rubus berries during postharvest phase (Harshman et al, 2014)…”
mentioning
confidence: 99%